The Factors Affecting the Entrepreneurial Intention of College Students - Primandaru, Noormalita (Faculty of Economics Universitas Negeri Yogyakarta in collaboration with the Institute for, 2017)
Abstract: The Factors Affecting the Entrepreneurial Intention of College Students. The alternative to solve an unemployment problem is to empower the educated person through entrepreneurship programs at colleges that are expected to contribute to employment, thereby reducing unemployment and the burden on the state. This study tested a model that aims to determine the influence of internal locus of control, social support and the need for achievement against in entrepreneurial intention of the student. This study was a cross-sectional. The results show a significant relationship between internal locus of control and social support to the entrepreneurial intention of students. There is a significant relationship between internal locus of control and the need for achievement of students. There is an insignificant relationship between social support and the need for achievement and the last there is a significant relationship between need for achievement and entrepreneurial intention of students. Keywords: internal locus of control, social support, need for achievement, entrepreneurial intentionAbstrak: Analisis Faktor-Faktor yang Berpengaruh pada Minat Berwirausaha Mahasiswa. Salah satu alternatif untuk memecahkan masalah pengangguran adalah dengan memberdayakan kelompok terdidik melalui program kewirausahaan di perguruan tinggi yang diharapkan mampu berkontribusi dalam penyerapan tenaga kerja sehingga mengurangi pengangguran dan beban negara. Penelitian ini menguji model yang bertujuan untuk mengetahui pengaruh internal locus of control, social support dan need for achievement terhadap minat berwirausaha pada mahasiswa. Penelitian ini termasuk dalam kategori penelitian cross-sectional. Hasil penelitian menunjukkan bahwa terdapat pengaruh internal locus of control dan social support pada minat berwirausaha mahasiswa, terdapat pengaruh internal locus of control terhadap need for achievement mahasiswa, tidak terdapat pengaruh social support pada need for achievement dan yang terakhir terdapat pengaruh need for achievement terhadap minat berwirausaha mahasiswa. Kata kunci: internal locus of control, social support, need for achievement, entrepreneurial intention